Herbs and Spices New Advances - Ivanišová, Eva (IntechOpen, 2023)
Phytotherapy is attracting increased interest for several reasons. It differs from medical procedures in that it uses the whole herb, although there is often only one component of the plant that works effectively to manage the problem. Plants contain many natural chemicals or phytochemicals that interact with the active ingredient and help prevent any side effects. Medicinal herbs and spices are investigated for their suitability in daily diets for maintaining general wellness or preventing disease. In the past decade, natural health products, dietary supplements, foods with added value, or nutraceuticals have emerged due to the increasing demand for non-pharmaceutical healthcare products. Medical herbs and spices are potential sources for developing new, effective, and safe ingredients to capture a rapidly expanding opportunity in global marketplaces. This book presents up-to-date information on the chemical, pharmacological, and nutritional uses of medicinal herbs and spices in folk medicine, pharmaceuticals, the food industry, veterinary practice, and gastronomy.